Teacher Collaboration: The Need for Trust in the Classroom Context - Willy Lima; Kadian Northover; Greogery Hewitt; Prof. Enid F. Newell-McLymont (International Journal of Engineering and Management Research, 2021)
Teacher coaching in schools takes various forms, but is commonly conceived as a means of providing personalised professional support to teachers through discussion about their practice (Lofthouse, Leat & Towler, 2010, p. 5). This paper fact resulted into a critical analysis of chapters two, four, and eight of the book "The Coaching Approach for Teaching and Learning" by Newell-McLymont (2015). For this reason, the paper reviewed Collaboration in the Classroom Context.Collaboration in the classroom context is a vital part of meeting the diverse needs of students in building an inclusive education system. Collaboration between teachers, parents, and specialists dealing with students with special needs in a context of school integration. Collaborative problem solving is a skill valued by the professional community, looking for people who can solve complex problems with their colleagues in the era of robotization of jobs. However, Collaboration remains a daunting challenge for students and professionals alike, where fairness, creativity, and people-to-people relationships can quickly become obstacles. Chapter four deals with the tools of cognitive coaching. These tools are the basis for the main ideas in this chapter. Some of these tools are "diagnostic" in nature Newell-McLymont (, 2015, p. 56-63). Finally, chapter eight of Newell-McLymont (2015) explores flexibility and the Nonjudgmental Nature of Cognitive Coaching. It has thus far been realized that the "cognitive coaching approach is a flexible approach for teaching and learning. It is "nonjudgmental" in nature. As a result, "trust can be established, and transformation can be experienced in the teaching and learning context" (p. 135). Where teacher-student relation is concerned, "whatever path a student may use to come up with a solution, the teacher can see it as valid or invalid and will be able to offer the necessary suggestions concerning its correctness" (p. 138). In the wake of the education reform, the school environment's renewal seems to be moving towards greater openness to working team consultation. Seen as a way to break isolation between teachers and other types of staff in complementary services, collaborative work can contribute to the overall development of students by ensuring better consistency in interventions.